Understanding The Freethinking Feminist Attack On Religion From A Feminist Perspective, Britain 1830-1870 - Benamer, Hamza . (University of Eloued جامعة الوادي, 2021)
This study seeks to refute the conventional view that associates atheism with Freethinking feminists on the one hand and to propose that their attack on religion was part of their wider agenda to rid society of false and repressive belief-systems and also as a means to promote women's rights on the other hand. The author argues that Freethinking women's decision to attack Christianity was not due to any lack of commitment to their faith, but because religion, in the end, contributed to the marginalisation of women in the social and political contexts. In fact, Freethinkers viewed the Christian Scripture as the founding text of female subordination, from which emerged all modern laws discriminating against women. Although were viewed as a liability, these 'infidel' feminists criticised, engaged with, and contributed to the wider women's suffrage movement, alongside the Christian values that dominated it. Based on this argument, Freethought needs to be written back into historiography as one of the few respectable feminist movements that gained reputability through its full rejection of false God-given notions of sexual difference and its wider commitment to supporting the woman question.
Keywords: Organised Freethought ; Freethinking feminists ; the attack on Scripture ; respectability ; female voting